Content analysis of educational videos of the second elementary mathematics course in the official content section of Shad Network from the perspective of paying attention to the standards of production of educational videos - tala sabbagh hasanzadeh; reza khoftedel (Shahid Chamran University of Ahvaz, 2022)
IntroductionThe introduction of technology and technologies in different sectors of the community has caused profound changes in them. The sentence of these sectors can be referred to the education sector. With the incidence of corona virus, the effect of using new technology and technologies in education was more important. But what is very important in this situation is the need for attention to the type of technology and quality of content through this New technologies producedMethodThe research method used in this research was descriptive and content analysis. The statistical research in this research is all educational films of primary school mathematics (fourth, fifth and sixth) in the official content section of the network. According to the subject of the sampling research, and the total statistical population was investigated. Information in this research is a checklist that was determined by the researcher design and validity by professors and experts in the field of electronic content. ResultsThe results showed that in the educational films of the mathematical lesson, the elementary school of the technical standards and the average of 3.3 to the average, the component of educational design standards with an average of 3.4 and a large amount of specific standards with an average of 2.9 and the average level was observed. It was found that technical and technical standards are more important than two other standards. DiscussionThe sudden prevalence of the corona virus has led to teachers to track and continue training to use cyberspace and educational films. But a point should be noted that in most manufacturing films to technical and technical features of the the results of this study are more important than other characteristics of the desirable educational film, moderate and quantitative attention. This reflects very little familiar familiar with the software and techniques of the educational film. Programs and specialized courses in this field can help increase the ability of teachers in educational film production. Performing this case and high teachers' domination will lead to the creation of desirable educational films that affect and maintain the quality of learning trend in non-existent training.